An assessment service delivery of Social Welfare Department dealing with vulnerable and disadvantages group in Perak - Mohamed Osman, Mariana; A. Bakri, Nurul Izzati; Bachok, Syahriah; Shuid, Syafiee (Elsevier, 2016)
A high-quality service delivery of Social Welfare Department (SWD) has encountered in promoting social inclusion towards the vulnerable and disadvantaged groups. This paper assesses the performance of SWD in the state of Perak, Malaysia by applied a semi-structured questionnaire survey of 400 respondents from a varied category of vulnerable and disadvantaged group within Perak. This research identified there is a correlation between service delivery performed and the quality of life of the respondents in social sustainability. The outcomes associated with strong justifications will offer alternatives to help in the betterment of the delivery system for these types of groups.